Fungal Cellulolytic Enzymes Microbial Production and Application (Springer Singapore, 2018)
The book provides an overview of the current knowledge on cellulolytic enzymes and their applications. It summarizes the mechanisms of synthesis and hydrolysis of cellulolytic enzymes, industrial fungal strains, genetic engineering of fungal strains and application of cellulolytic enzymes. This book will be a useful reference for researchers and bioengineering experts engaged in lignocelluloses biodegradation, biomass utilization, enzyme production and fungal molecular biology. .